Effects of tocilizumab versus hemoadsorption combined with tocilizumab in patients with SARS-CoV-2 pneumonia: Preliminary results. Issue 1 (January 2022) - Berlot, Giorgio; Pintacuda, Stefania; Moro, Edoardo; Paluzzano, Giacomo; Scamperle, Alice; Chillemi, Antonino; Longo, Irene; Dattola, Roberto; Roman-Pognuz, Erik; Tomasini, Ariella
Objective: To assess the variations of Interleukin-6 (IL-6) in patients with SARS-CoV-2 infection treated with Tocilizumab (TCZ) alone or in association with hemoadsorption (HA). Design: Retrospective. Setting: An Intensive Care Unit (ICU) admitting mechanically ventilated patients with SARS-CoV-2 pneumonia. Patients: Four adult patients. Interventions: We compared the blood values of IL-6, C-reactive protein (CRP) and of other biochemical variables including the PaO2 /FiO2 in two patients who received TCZ alone and in other 2 in whom it was associated with the HA (TCZ-HA) due to the presence of impending or established organ failures other than the lung. All variables were measured before, during and after the treatment. Main results: In all patients, the IL-6 increased during the treatment; after its termination, its values sharply decreased only in those treated also with HA; conversely, the CRP decreased in all patients; the PaO2 /FiO2 increased in three patients and remained stable in the remaining one. Both the TCZ and the HA were well tolerated; all patients were weaned from the mechanical ventilation and discharged from the hospital. Limitations: Although the limited number of patients does not allow to draw firm conclusions, the increase of the IL-6 of can be ascribed to its displacement from cellular and soluble receptors, whereas its decrease is likely due to the scavenging effect exerted by the HA. Although the association TCZ-HA could be valuable in the treatment of the Cytokine Release Storm (CRS) associated with the SARS-CoV-2, the HA could be more effective as it neutralizes a wider panel of inflammatory mediators.